Formation of tolerance to other cultures as a component of professional training of future managers for intercultural interaction in content and language integrated learning - Irina Evgenievna Kuteneva (Вестник Майкопского государственного технологического университета, 2023)
Today, in connection with the aggravation of the international situation, teaching tolerance is of particular relevance. Currently, there is a contradiction between the tendencies towards globalization and the isolation of cultures, therefore, the problem of establishing intercultural ties and building an equal dialogue of cultures is acute. The aim of the research is to analyze the role of developing tolerance towards other cultures in preparation for intercultural interaction. In the research the author uses the method of analysis of scientific literature and diagnostic techniques. As a result of the experiment, the positive influence of the development of tolerance to other cultures on the preparation for intercultural interaction has been revealed. Thus, we can draw key conclusions that: preparation for intercultural interaction helps to overcome psychological barriers in learning a foreign language, promotes the disclosure of the student’s personality, creates a healthy atmosphere in the student community and stimulates further learning; tolerance education should be more widely applied in educational institutions of various levels as the prevention of extremism in a tense intercultural environment.